Spatial ecological-economic analysis for wetland management : - Bergh, Jeroen C. J. M. van den (Cambridge University Press, 2004)
World wetlands are endangered by human activities and development in all parts of the world. This book approaches the study of wetlands management and development policy by using integrated ecosystem modelling that draws on insights from hydrology, ecology and economics.